Improving Science Literacy Skills of Phase B Elementary School Learners through Problem Based Learning and Differentiated Strategies - Raisa, Raisa Okta Peni; Rina Heryani (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Students’ science literacy is often low due to teacher-centered learning activities. This study aims to analyze the impact of Problem Based Learning (PBL) model with differentiation strategy on improving students’ science literacy. Through a quasi-experimental design (one-group pre-test post-test) involving third grade students in one of Cimahi City elementary schools, it was found that the implementation of PBL model with differentiation strategy significantly improved science literacy skills. This is indicated by the increase in the average score from 57.00 (pre-test) to 71.20 (post-test), as well as the results of a paired sample t-test with a value of p < 0.001 which shows significance. These findings indicate that the combination of PBL model with differentiation strategy provides benefits in improving concept understanding, learning motivation, and active involvement of students in science learning. Therefore, this approach is recommended to be implemented in elementary schools to increase the effectiveness of science learning more optimally and in accordance with the needs of students.